A game without penalty: Purchasing a professional club, a rational crime? - Carin, Yann; Terrien, Mickael (Quality in Sport, 2020)
This paper aims to advance a new strategic explanation for the detention of a professional football club based on criminal motivations. Despite recurring deficits, most of the French professional football teams have changed owner over the last years (22 of 40 since 2010). It is therefore difficult at first sight to understand why investors are attracted to this industry. Beyond the internal / external distinction, this article advances a new explanation based on economics of crime. Semi-structured interviews were performed and primary data was analyzed to explain that purchasing a professional football club for criminal ends would be rational. The removal of the Third Party Ownership may explain some of this phenomenon. Results also suggest that the football industry is a criminogenic market. From this, it was possible to derive consequences of the potential criminal behavior of the new investors and managerial recommendations to fight against this existing situation.